NILAI FILOSOFIS MASJID 99 KUBAH DI KOTA MAKASSAR - Anggraeni, A. Milandriani; Taslim, Mubarak; Veranita Indah, Astrid (Sulesana, 2025)
This research is motivated by the growing phenomenon of modern mosque construction that not only functions as a place of worship, but also as a cultural symbol, religious tourism, and a means of spiritual education. The 99 Dome Mosque in Makassar City, which attracts attention because of its unique architecture as well as the philosophical meaning contained within it. The emergence of this mosque raises questions about how Islamic values ​​and religious symbols are realized in a modern architectural form that remains rooted in spiritual meaning. Based on this, this research focuses on two main problem formulations, namely the background of the construction of the 99 Dome Mosque and what philosophical values ​​​​are contained within it. This research is expected to uncover the deep meaning of the design, function, and religious symbols that make this mosque a representation of harmony between architecture, spirituality, and philosophical values ​​​​in the midst of modern developments